Investigation of vibration in micromilling with MQL: S/N ratio analysis - Hussin, Muhammad Shaffiq; Ali, Mohammad Yeakub; Banu, Asfana; Abdul Rahman, Mohamed; Chowdhury, Md. Sazzad Hossien (TEST Engineering & Management, 2020)
Micromilling process equipped with minimum quantity lubrication (MQL) is proven to significantly reduce the cutting temperature during machining and improve the life of the cutting tool. However, undesired vibration known as chatter remains as an unsolved issue in micromilling especially with the presence of MQL. The objective of this research is to present the signal-to-noise (S/N) ratio analysis of the effect of MQL and micromilling parameters towards the vibration in micromilling. High-precision CNC machine tool (DT-110 Mikrotools, Singapore) was used to machine microchannels onto a copper workpiece (C1100) with a 500 µm diameter end milling tool lubricated with MQL system (Fuji-BC Engineering, Japan). Machining parameters spindle speed, depth of cut, oil flow rate, nozzle air pressure, and nozzle direction were experimentedusing Taguchi L16 Orthogonal Array design. The responses were spindle speed frequency (SSF) amplitudes and SSF chatter amplitude which were measured using an accelerometer (Dytran, USA) and a data acquisition system (Graphtec, Japan). From the amplitudes, chatter ratio was calculated and analysed using S/N ratio. The analysis showed that the spindle speed, nozzle direction, and nozzle air pressure have significant effect towards chatter followed by depth of cut and oil flow rate. The optimum parameter suggested by S/N ratio were found to be 20000 rpm spindle speed, 275° nozzle direction, 0.275 MPa nozzle air pressure, 50 µm depth of cut, and 3.75 ml/hr oil flow rate.